The trouble with May Amelia - Holm, Jennifer L. (Atheneum Books for Young Readers, 2011)
Living with seven brothers and her father, who thinks girls are useless, a thirteen-year-old Finnish American farm girl is determined to prove her worth when a enterprising gentleman tries to purchase their cash-strapped family settlement in Washington State in 1900.